La educación ambiental y conciencia ambiental en estudiantes de la Universidad Nacional de la Amazonía Peruana UNAP 2022 - Carranza Gonzales, Javier (2024)
The reason behind conducting this research was to assess the relationship between environmental education and environmental awareness variables in first and fifth-level students of the Environmental Management Engineering program. As part of the stated objectives, the study aimed to identify knowledge levels in first and fifth-level students and determine detailed score differences between the two levels. This study follows a cross-sectional prospective design, specifically a non-experimental correlational approach, with a sample population of 110 students from the Environmental Engineering program at the National University of the Peruvian Amazon. Data collection involved survey techniques and the application of a questionnaire as a validated tool based on expert judgment. The findings indicate a significant association between the study variables, environmental education, and environmental awareness, with a p-value < 0,05. However, the relationship observed is characterized as low, direct, and positive. The Mann-Whitney U analysis demonstrated no significant differences in scores between first-level and fifth-level students, with a p-value > 0,05.